Dhea Use to Improve Likelihood of Ivf/Icsi Success in Patients with Diminished Ovarian Reserve: A Systematic Review and Meta-Analysis - Schwarze-Meza, J (SBRA - Associação Brasileira de Reprodução Assistida (Brazilian Society of Assisted Reproduction), 2018)
The aim of this review is to determine if the use of DHEA increases the likelihood of success in patients with POR. We searched MEDLINE and EMBASE using the terms "DHEA and diminished ovarian reserve", "DHEA and poor response", "DHEA and premature ovarian aging". A fixed effects model was used and Peto s method to get the odds ratio (OR) with 95% confidence intervals (CI 95%). For quantitative variables, Cohen s method was used to present the standardized mean differences (SMD) with their corresponding confidence intervals. Only five studied fulfilled the selection criteria. DHEA was administered in 25 mg doses, three times a day. In all studies, the authors corrected for the presence of confounding variables such as partner s age, infertility diagnosis and number of transferred embryos. The meta-analysis of the five selected studies assessed a total of 910 patients, who underwent IVF/ICSI, of which 413 had received DHEA. DHEA use was associated with a significant increase in pregnancy likelihood (OR 1.8, CI 95% 1.29 to 2.51, p=0.001). When analyzing the association between DHEA use and the likelihood of abortion, we found low heterogeneity between studies (I2=0.0%) and the use of DHEA to be associated to a significant reduction in the likelihood of abortion (OR 0.25, CI 0.07 to 0.95; p=0.045). Analysis of the association of DHEA with average oocyte retrieval showed high variability between studies (I2=98.6%), as well as no association between DHEA use and the number of oocytes retrieved (SMD-0.01, CI 95%-0.16 to 0.13; p>0.05). © 2018, Sociedade Brasileira de Reproducao Assistida. All rights reserved.